Learning Interest in Stie Semarang Accounting Students During Covid 19 Pandemic (Universitas Negeri Semarang, 2022)
This study aims to determine whether online learning, Educational Technology carried out by lecturers at STIE can increase student interest in learning about effective subjects. The population in this study were accounting students at the Sekolah Tinggi Ilmu Ekonomi Semarang, 126 Students, and 40 samples were obtained using a purposive sampling technique. The method used in this research is multiple regression analysis. The results of this study indicate that online learning has no significant effect on learning interest. Meanwhile, education technology has a significant effect on interest in learning. The value of the determinant coefficient obtained is 0.336, meaning that 33.6% of learning interest is influenced by online learning and educational technology. For future research, it is recommended to add other independent variables such as online learning methods, information technology and online learning media to complement this research further because there are other independent variables outside of this study that might affect interest in learning. Students are expected to maintain good learning. Hopefully, educational technology can be improved because these variables are the most influential and significant on learning interest.